The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1089/pop.2018.0089
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Access Barriers Bring Children to Emergency Rooms More Frequently: A Representative Survey

Abstract: Children may visit the emergency department (ED) regularly in part because they and their caregivers may be experiencing barriers to appropriate and timely pediatric care. However, assessing the wide range of potential barriers to access to care that children and their caregivers may experience is often a challenge. The objective of this study was to assess the barriers to pediatric health care reported by caregivers and to examine the association between those reported barriers to care with the frequency of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Caregivers who experienced cultural or language barriers were 5.8 times more likely to take their child to the ED more than twice within the period of 12 months compared with children who did not have caregivers who experienced cultural or language barriers. 29 Transport challenges were also correlated with numerous ED visits. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Caregivers who experienced cultural or language barriers were 5.8 times more likely to take their child to the ED more than twice within the period of 12 months compared with children who did not have caregivers who experienced cultural or language barriers. 29 Transport challenges were also correlated with numerous ED visits. 22 …”
Section: Resultsmentioning
confidence: 99%
“…11 In addition, studies have shown a strong association between SDoH and ED utilization. 12,13 For example, during the first year of life, children who experienced homelessness were significantly more likely to visit the ED. 14 Using insurance billing data for an adult sample, 1 study found that patients with incomes less than the national median had a significantly increased risk of ED visits for hypoglycemia in the last week of the month (when food benefits would be expected to run out) compared to earlier weeks.…”
Section: Importance Of Sdoh In the Emergency Departmentmentioning
confidence: 99%
“…A recent systematic review found a high prevalence of material needs among patients in several ED studies 11 . In addition, studies have shown a strong association between SDoH and ED utilization 12,13 . For example, during the first year of life, children who experienced homelessness were significantly more likely to visit the ED 14 .…”
Section: Importance Of Sdoh In the Emergency Departmentmentioning
confidence: 99%
“…Previous studies have found that children who live below the poverty line are prone to have poor health and chronic health conditions, which require more medical attention. 20 However, these children may not be able to access preventive care due to lack of transportation 21 or inability of the parents to take time off if the scheduled medical appointment conflicts with their working hours.…”
Section: Discussionmentioning
confidence: 99%